E-Learning as an Important Component in "Blended Learning" in School Development Projects in Norway - Aasen, Ann Margareth (International Journal of Advanced Corporate Learning (iJAC), 2013)
E-learning is an important component in â??blended learningâ? in all of SePU`s projects and is used for additional education and development of competences. Blended learning is defined as learning facilitated by the effective combination of different modes of delivery, models of teaching, styles of learning, and based on transparent communication among all parties involved in development competences. In general, one of the challenges with improving the workplace is linked to employee training and development of competences. Training is often costly in terms of time, finances, and organization. In accordance to these challenges, educational development is not be limited to training carried out at educational institutions on training days but within the limits and resources available at workplaces. All projects are based on an understanding of learning as a process where you learn by collaborating with others. Collaboration is to be distinguished from cooperation. In cooperation, partners split the work, solve sub-tasks individually, and then assemble the partial results into the final output. In collaboration, partners do the work together. E-learning can therefore contribute to improved flexibility in human resource development and lifelong learning.